PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH LUAR BIASA NEGERI TENGGARONG KABUPATEN KUTAI KARTANEGARA - Fajar Hariyanto (ADMINISTRASI PUBLIK, 2019)
SLB educational institutions are professional educational institutions, which aim to form learners who have physical and mental disorders in order to be able to develop skills in the world of work or follow further education. To improve the teacher's performance, the headmaster has several very important roles. Among them are being able to delegate authority appropriately, create a harmonious working atmosphere, motivate and build the spirit of participation in all school activities, and have a person who is exemplary. The purpose of the research was to find out how the headmaster's leadership influenced the performance of teachers of SLB Negeri Tenggarong Kutai Kartanegara Regency. This research is a research with verifikatif research or causality, namely research that looks for causal relationship between Independent variable (X) and Dependent variable (Y). The population in the study was 27 teachers. Sampling techniques using census methods. Data collection techniques using documentation methods and questionnaires. The analysis tools used are Product Moment Coefficient Analysis (Pearson) and hypothesis testing using t-tests with the help of SPSS 17.0 for Windows. The result of this study is that there is a very strong relationship /correlation between the principal leadership variable (X), and the Teacher Performance (Y) in SLB Negeri Tenggarong of 0.675 or has an influence of 45.5%. This means that if the headmaster's leadership is good enough then the teacher's performance looks good.